Indirect arterial blood pressure measurement: review - Arcuri, Edna Apparecida Moura (1989)
This study deeds with the indirect arterial blood pressure measurement, particularly the American Heart Association recommendations for sphygmomanometry References are made regarding the ratio arm circumference/cuff width and the errorseaused by inadequate cuff size. Several variables envolved in the procedure of arterial blood pressure measurement are discussed.